2021
DOI: 10.31219/osf.io/sh7ja
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting Romantic Interest during Early Relationship Development: A Preregistered Investigation using Machine Learning

Abstract: There are massive literatures on initial romantic attraction and established, “official” relationships. But there is a gap in our knowledge about early relationship development: the interstitial stretch of time in which people experience rising and falling romantic interest for partners who have the potential to—but often do not—become sexual or dating partners. In the current study, 208 single participants reported on 1,065 potential romantic partners across 7,179 data points over seven months. In stage 1 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 111 publications
0
8
0
Order By: Relevance
“… 39 ), first impressions are also bound to change, as reflected by the overall small-to-moderate effect sizes in the current study. For example, research suggests that relationship effects wax and partner effects wane as people get to know each other ( 14 , 40 ). Future studies should incorporate how impressions change during relationship initiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 39 ), first impressions are also bound to change, as reflected by the overall small-to-moderate effect sizes in the current study. For example, research suggests that relationship effects wax and partner effects wane as people get to know each other ( 14 , 40 ). Future studies should incorporate how impressions change during relationship initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Although these datasets have been in previous publications (e.g., refs. 25 , 29 , 30 , 40 , 43 ), no prior articles used initial desire (measured at speed dating) to prospectively predict relationship initiation (measured during the follow-up period), as was done in the current study.…”
Section: Methodsmentioning
confidence: 99%
“…The established relationships machine-learning study (Joel et al, 2020) reported that the addition of individual differences to the perceiver’s perception of their relationship with the target accounted for less than 1% of the variance in satisfaction and commitment. Another study (Eastwick et al, in press) examined an early relationship development context in which perceivers were reporting on targets in whom they were romantically interested (i.e., potential romantic partners, crushes). In this study, Perceiver individual difference × Perception of target interactions accounted for 3% of the variance.…”
Section: Two Principles Seven Predictionsmentioning
confidence: 99%
“…These two approaches encompass most empirical tests of moderation by individual differences (i.e., Perceiver × Target interactions); such hypotheses are ubiquitous in the literature and are commonly derived from a wide variety of close relationships (e.g., Girme et al, 2021; Luerssen et al, 2017; Wang et al, 2021) and evolutionary psychological (e.g., Brown & Sacco, 2017; Lamela et al, 2020; Meltzer et al, 2014) perspectives (cf. Eastwick et al, in press).…”
Section: The Components Of Met In Detailmentioning
confidence: 99%
“…Human mating researchers have also measured functional preferences, albeit less commonly than summarized preferences. For instance, in one set of studies (Brumbaugh & Wood, 2013; Wood & Brumbaugh, 2009), researchers computed participants' functional preferences as the within‐person correlation of (a) the level of an attribute depicted in each of a set of faces (e.g., “confident”) with (b) the participant's attraction ratings to each face (see also DeBruine et al, 2006; Eastwick et al, in press).…”
Section: Introductionmentioning
confidence: 99%